Kronološki pregled motivike o svetih bratih Cirilu in Metodu v slovenskem pesnjenju - Stanonik, Marija (Edinost in dialog, 2014)
Chronological intersection of the motifs of the holy brothers Cyril and Methodius in the Slovenian poetry from 1832 to 2007 covers over eighty units. If we consider texts combined in cycles the total number of these texts is close to 100. Most of the songs originated in the 19th century to commemorate the 1000th anniversary of the arrival of Slavic Apostles to Moravia and Lower Pannonia (863) as well as in between the creation in memory of the holy brothers never dried up. Maximum attention is devoted to the motifs and partly to the spiritual message while the formative and stylistic questions wait for a greater depth in the detailed analyses. Due to the extensive material the contribution has been divided into two parts.
Keywords: Cyrillus, svetnik, 826-869; Methodius, svetnik, 815-885; slovenska poezija; literarni motivi; svetniki